1997
DOI: 10.1093/infdis/175.1.172
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Virus Load during Pregnancy and Mother-to-Child Transmission of Human Immunodeficiency Virus Type 1: The French Perinatal Cohort Studies

Abstract: Virus load in pregnancy and its relation to mother-to-child human immunodeficiency virus (HIV) transmission were studied prospectively. From 1989 to 1994, 320 HIV-infected women from 18 centers had plasma samples stored. Among women not receiving antiretroviral therapy, the polymerase chain reaction RNA level was 3.6 log at delivery, and 15% of women had levels below the detection limit. There was no variation during pregnancy. Women born in sub-Saharan Africa had lower RNA levels, although their CD4 cell dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
5

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(73 citation statements)
references
References 11 publications
5
63
0
5
Order By: Relevance
“…Additionally, the extended interval between laboratory assessment and delivery time is a limitation that may potentially compromise our findings and conclusions. Despite the significant difference between mean viral load in mother to child transmission and non-mother to child transmission, a threshold for predicting mother to child transmission was not established, similar to other studies (Mayaux et al 1997, Garcia et al 1999, ECS 2005, Read et al 2007.…”
Section: Discussionmentioning
confidence: 54%
“…Additionally, the extended interval between laboratory assessment and delivery time is a limitation that may potentially compromise our findings and conclusions. Despite the significant difference between mean viral load in mother to child transmission and non-mother to child transmission, a threshold for predicting mother to child transmission was not established, similar to other studies (Mayaux et al 1997, Garcia et al 1999, ECS 2005, Read et al 2007.…”
Section: Discussionmentioning
confidence: 54%
“…Our key finding is that the level of HIV viral load is ≥ 4log 10/ml in more than 60% of HIV pregnant women, ignorant of HAART, with CD4 cell count > 350/mm 3 , making them eligible for maternal triple ARV prophylaxis as required elsewhere. Taking into account that an average of 4 in 10 HIV positive pregnant women are yet to be eligible for HAART because of CD4 cell count of < 350/mm 3 , it may be deduced that among the remaining 6 in 10, at least 4 may require HAART for prophylaxis according to their HIV viral load. Altogether 8 in 10 women at least may be eligible for HAART during pregnancy based upon biological criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Results were produced in absolute numbers and in percentages. CD4 cell count screening was followed by non exclusive measurement of viral load when CD4 cell counts were > 350/mm 3 . Maternal baseline serum samples were quantified for HIV-1 RNA load using real Time reverse transcriptase PCR (Generic HIV viral load, Biocentrics).…”
Section: Study Population and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Because ZDV therapy has little effect on maternal virus levels and ZDV is effective in reducing transmission regardless of the maternal HIV-1 RNA copy number in plasma, it is believed that a significant portion of the protection is due to chemoprophylaxis in the newborn following exposure to the virus, rather than to a reduction of virus levels in the maternal blood (3,12,27,28,38). Further evidence for this chemoprophylactic mechanism was provided by a recent study in Uganda which demonstrated that the rate of perinatal HIV transmission was greatly reduced by administration of two doses of nevirapine, the first given to the mother in labor and the second given to the infant shortly after birth (16).…”
Section: Simian Immunodeficiency Virus (Siv) Infection Of Newborn Macmentioning
confidence: 99%